PENGARUH CORPORATE SOCIAL RESPONSIBILITY, CAPITAL INTENSITY, DAN CORPORATE GOVERNANCE TERHADAP AGRESIVITAS PAJAK - Neno Neno; Wiwit Irawati (LPPM Universitas Putera Batam, 2022)
This study aims to determine the effect of Corporate Social Responsibility, Capital Intensity, and Corporate Governance on Tax Aggressiveness in Non-Cyclical Consumer Manufacturing Companies Listed on the Indonesia Stock Exchange in 2016-2020. The population in this study used manufacturing companies in the Consumer Non-Cyclical sector as many as 93 companies. The sampling method in this study used a purposive sampling method, in order to obtain a sample of 15 manufacturing companies in the Consumer Non-Cyclicals sector. Sources of data used in this study is secondary data. Data analysis was performed using Eviews 9. The results of the simultaneous study of Corporate Social Responsibility, Capital Intensity, independent commissioners and audit committees have an effect on tax aggressiveness. Partially Corporate Social Responsibility has a significant and negative effect on tax aggressiveness, Capital Intensity, independent commissioners and audit committees have no significant effect on tax aggressiveness.